Chorea as the First Manifestation of Cerebral Infarction - Hernandez Fustes, Otto Jesus (Cureus, 2020)
Cerebrovascular disease (CVD), which usually manifests as a focal neurological deficit, is presented here as a movement disorder. This unusual manifestation corresponds to 1% of the CVDs and 8% of the striatal lesions. We report a 37-year-old right-handed woman who developed choreic movements as the first manifestation of an acute stroke. The computed tomography (CT) scan revealed a cortical/subcortical hypodense lesion in the right middle cerebral artery territory. This picture slowly improved and remitted completely after six weeks. Basal ganglia infarcts are crucial for the development of hemichorea, however, in spite of its frequency, movement disorders are disproportionally rare. In the majority of cases, the prognosis is good with spontaneous remission after two to four weeks.